Delineation of groundwater potential zones in rocky aquifers in the mountainous area of Central Nepal (Journal of Nepal Geological Society, 2016)
Groundwater is the lifeline for the people residing in the mountainous regions of Nepal as they are dependent in this natural resource for drinking and other domestic purposes. The springs and seepages are reported to be drying in many places in Nepalese mountains in the recent time. Such problem is expected to be much more severe in view of climate change condition in the future. In this regard, it is important to establish a methodology to explore groundwater in the mountainous terrain for better planning. In order to delineate groundwater potential zones of rocky aquifers in the mountainous terrain, study has been carried out in Melamchi watershed, lying in the Sindhupalchowk district, Nepal. Various thematic layers have been prepared in GIS and the satellite imageries have been used to extract relevant information. Ranks and weights have been assigned to each thematic layer and its classes, respectively. The rasterized layers have been combined and classifi ed and the resulting map is crossed with the existing springs. It is found that the moderate and high potential classes of the groundwater potential map are represented by the existing springs. This method is expected to be useful at the preliminary watershed level study of groundwater potential in the mountainous terrain of central Nepal.